Treatment Satisfaction With Couplelinks Online Intervention to Promote Dyadic Coping in Young Couples Affected by Breast Cancer - Fergus, Karen; Tanen, Adina; Ahmad, Saunia; Gardner, Sandra; Warner, Ellen; McLeod, Deborah; Stephen, Joanne; Carter, Wendy; Periera, Amanda (Frontiers in Psychology, 2022)
Background This study evaluated participant satisfaction with “Couplelinks,” an online psychological intervention designed for younger couples coping with breast cancer. The program included six experiential learning exercises (plus one optional module), psychoeducational information, and support from a personal mental health professional. Objective The primary objectives were to examine participants’ perceptions of: the online intervention’s structure and content; the value of including a professional facilitator; and benefits and drawbacks of the program. Methods A treatment satisfaction questionnaire comprised of Likert indices and open-ended questions pertaining to treatment satisfaction was completed by 26 patients and 27 male partners (N = 53) approximately 1–2 weeks following the intervention which occurred in the context of a randomized controlled trial. Descriptive statistics were used to summarize satisfaction ratings and generalized linear models with fixed effect for gender were used to test for differences in male-female outcomes. A thematic analysis was undertaken in order to understand, organize and summarize the qualitative textual feedback. Results Participants reported an overall satisfaction rating of 4.3 out of 5 (SD = 0.54) with patient satisfaction ratings being higher than that of male partners’ (p = 0.01). The majority of participants considered the facilitator’s role to be necessary 4.6 (SD = 0.60), and found the program to be convenient 4.1 (SD = 0.81) despite some participants struggling to keep up with the modules. Subjective data revealed participants valued the convenience and flexibility of the online intervention and appreciated the program’s involvement of both partners. Participants also reported that including a professional facilitator humanized the intervention, served as motivation to progress through the program, facilitated insight into their relationship, and was reassuring. Experiential gains noted by participants included that the program: helped couples to open channels of communication; prompted them to designate quality time for one another; evoked feelings of unity and togetherness; and inspired new insight in the relationship. Conclusion Such feedback supports the feasibility and acceptability of the Couplelinks program while offering directions for improvement of online couple-based interventions in cancer.